Mourning the dead, mourning the disappeared: The enigma of the absent–presence. (1st November 2014) - Taiana, Cecilia
Abstract : Freud's interest in the impact of death on the living goes back further than Mourning and Melancholia (1917e, [1915]). In Totem and Taboo (1912–13) Freud noted the ambivalence of the emotions we experience in relation to the dead. In this paper, I focus on Mourning and Melancholia as a landmark in the understanding of both the normal and psychopathological aspects of mourning and depressive processes in human beings . Mourning and Melancholia bridges Freud's first and second topographic theories of the psychic apparatus and constitutes for many authors the foundation of his theory of internal object relations. With this psychoanalytic understanding of mourning as a framework, I discuss 'special mourning processes, ' such as the those confronted by psychoanalysts in Argentina when treating the relatives of thousands of people who were 'disappeared' by the military dictatorship in the 1970s; they are 'special' in the sense that the external reality [which] constitutes the starting point of the psychic mourning process, as described by Freud, is absent. I argue that the 'absent–presence' of the body as an enigmatic message initiates a special mourning process that bears certain characteristics of, and is isomorphic to, Laplanche's seduction theory .